2017
DOI: 10.1044/2016_jslhr-l-15-0384
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cognitive Ability on Therapy Outcomes for Anomia in Adults With Chronic Poststroke Aphasia

Abstract: Purpose:The relationship between cognitive abilities and aphasia rehabilitation outcomes is 2 complex and remains poorly understood. This study investigated the influence of language 3 and cognitive abilities on anomia therapy outcomes in adults with aphasia. 4Methods: 34 adults with chronic aphasia participated in Aphasia Language Impairment and 5Functioning Therapy. A language and cognitive assessment battery, including 3 baseline 6 naming probes, was administered prior to therapy. Naming accuracy for 30 tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 77 publications
3
69
2
1
Order By: Relevance
“…There is evidence that some cognitive functions are more likely to improve with exercise, 51 and that only certain cognitive functions are related to aphasia treatment outcomes. 16 Future studies should include pre-and post-treatment assessments of a broad range of cognitive functions to enhance our understanding of the relationship between aerobic exercise, cognitive functions, and treatment outcomes in aphasia rehabilitation.…”
Section: Considerations Related To Behavioral Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence that some cognitive functions are more likely to improve with exercise, 51 and that only certain cognitive functions are related to aphasia treatment outcomes. 16 Future studies should include pre-and post-treatment assessments of a broad range of cognitive functions to enhance our understanding of the relationship between aerobic exercise, cognitive functions, and treatment outcomes in aphasia rehabilitation.…”
Section: Considerations Related To Behavioral Interventionmentioning
confidence: 99%
“…10,11 Indeed, studies of the predictors of response to aphasia treatment have demonstrated that nonlinguistic cognitive abilities are related to success in naming therapy. [12][13][14][15][16] This observation suggests that PWAs with other cognitive deficits may be less likely to acquire and maintain therapeutic benefit from naming treatment without an approach that also aims to improve cognitive functions. As language and other cognitive functions are supported by overlapping brain regions, the functions of which have been shown to improve with long-term exercise, 17 there is support for considering long-term exercise as an adjuvant to aphasia treatment.…”
Section: Introductionmentioning
confidence: 99%
“…16 Indeed, a recent study investigated several different cognitive domains and found a strong effect of verbal short-term memory on participants' treatment gains when completing anomia therapy (as measured by their change in naming accuracy post-therapy). 17 Dysarthria treatment studies that focus on average results from groups of speakers cannot easily quantify these individual effects. Hence, although there is a high prevalence of depression and cognitive impairment in speakers with dysarthria, [18][19][20] individuals with significant cooccurring difficulties are often excluded from studies to promote consistency across the treatment group.…”
mentioning
confidence: 99%
“…Finally, the patient did not exhibit any mental rotation disorders, but processing duration increased after rehabilitation, which could be linked to the decline in mood related to his personal life situation at the time of the assessment. As mentioned in previous studies, it is necessary to maintain the integrity of some cognitive abilities (verbal and visuo-spatial shortterm memory, working memory, executive function) because of their impact on aphasia severity, language function and its recovery (Dignam et al, 2017;Fonseca et al, 2017;Seniów et al, 2009). Indeed, deficits in memory, executive functions, speed processing have been shown to be associated with an increase of aphasia severity (Fonseca et al, 2018).…”
Section: Discussionmentioning
confidence: 94%